Elucidation of rheological properties of frozen non-fermented dough with different thawing treatments: The view from protein structure and water mobility. (November 2022) - Yang, Jingjie; Chen, Li; Guo, Boli; Zhang, Bo; Zhang, Yingquan; Li, Ming
Abstract: The objective of this study was to elucidate the rheology differences between the dough with different thawing methods in terms of protein structure and water mobility. The frozen dough samples were thawed by three methods: refrigerator (4 °C), proofer (25 °C, 85% RH), and microwave (1000W), respectively. Results showed that the rheological properties of doughs produced by refrigerator and proofer-thawing were closer to untreated dough than that produced by microwave thawing. Contrastingly, microwave-thawing produced doughs with a harder and less elastic texture. Besides, refrigerator and microwave thawing tended to have highest and lowest percentage of large polymeric proteins (LPP), respectively. A significant decrease in the proportion of α -helices, accompanied with the increased β -sheets and random coils was obtained from the microwave thawing group ( P ＜ 0.05 ). Furthermore, microwave-thawing had the biggest impact on water mobility and distribution, followed by proofer and refrigerator-thawing. The refrigerator-thawing produced dough samples with a more intact inner structure, indicating less damage and impact on the quality of dough. Graphical abstract: Image 1 Highlights: 1.In our study, a refrigerator thawing was optimum for non-fermented dough. 2.Thawing with optimum conditions, the dough had better rheological properties. 3.More disrupted and weak gluten structure were observed microwave-thawing dough. 4.Microwave thawing drove more water conversion towards a mobile one than others.